Characterization of Tn5801.Sag, a Variant of Staphylococcus aureus Tn916 Family Transposon Tn5801 That Is Widespread in Clinical Isolates of Streptococcus agalactiae - Mingoia, Marina (American Society for Microbiology, 2013)
Tn5801, originally detected in Staphylococcus aureus Mu50, is a Tn916 family element in which a unique int gene (int(5801)) replaces the int and xis genes in Tn916 (int(916) and xis(916)). Among 62 tet(M)-positive tetracycline-resistant Streptococcus agalactiae isolates, 43 harbored Tn916, whereas 19 harbored a Tn5801-like element (Tn5801.Sag, ∼20.6 kb). Tn5801.Sag was characterized (PCR mapping, partial sequencing, and chromosomal integration) and compared to other Tn5801-like elements. Similar to Tn5801 from S. aureus Mu50, tested in parallel, Tn5801.Sag was unable to undergo circularization and conjugal transfer.